Diagnostic bronchoscopy: an experience in a hospital of limited resources - Singh, Chingakham Debeshwar; Wilubuibou, P.; Singh, Thounaojam Amusana (International Journal of Research in Medical Sciences, 2018)
Background: Diagnostic bronchoscopy is conventionally performed in evaluating undiagnosed abnormal chest x-ray findings, undiagnosed haemoptysis, pleural effusion, unexplained cough and collapse of lung etc. One indispensable use currently is for diagnosis of lung cancer. The aim of the study was to study the various types of patients who have undergone Diagnostic Bronchoscopy in a hospital of limited resources and the diagnostic outcomes of the procedures. Methods: A retrospective study of Bronchoscopies was done from October 2016 to January 2018, in Department of Respiratory Medicine in the hospital of a Medical College. All 178 patients of all age and any sex were included in the study. These patients present in the study had chest X-ray and CT scan of thorax. Other investigations done were ZN stains for AFB and CBNAAT-TB (Cartridge Based Nucleic Acid Amplification Test) for sputum and blood complete haemogram, prior to bronchoscopy. Results: Our study has shown that Diagnostic bronchoscopy is particularly useful in diagnosis of lung cancer, sputum smear negative Tuberculosis, if proper selection of cases is done even in a centre of limited resources. It has become an absolute necessity in a medical college hospital. Conclusions: Bronchoscopy in our resource limited set up shows that it is an indispensable tool for diagnosis of lung cancer with patients with clinical presentations of lung collapse, unresolved consolidation, lung masses, undiagnosed pleural effusions and haemoptysis. The usefulness can be much better if facilities like TBNA, EBUS are made available.